Post‐traumatic stress disorder in Stevens–Johnson syndrome and toxic epidermal necrolysis: prevalence and risk factors. A prospective study of 31 patients. (3rd December 2018) - Hefez, L.; Zaghbib, K.; Sbidian, E.; Valeyrie‐Allanore, L.; Allain, M.; Duong, T.A.; Colin, A.; Bellivier, F.; Romano, H.; de Prost, N.; Chazelas, K.; Chosidow, O.; et al.
Summary: Background: Epidermal necrolysis is a rare and severe cutaneous adverse reaction to drugs with long‐term somatic consequences and potentially underrecognized psychological complications. Objectives: To assess the prevalence and risk factors of post‐traumatic stress disorder (PTSD) in Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) in a population of adults undergoing psychiatric evaluation. Methods: In this prospective study, we included adult patients admitted at the acute phase of SJS/TEN to our dermatology department from June 2009 to February 2013. The main objective was to assess the prevalence of PTSD at 6 months after the acute disease phase, defined by a PTSD Checklist score > 44. Secondary objectives were to investigate risk factors of PTSD in the medical history of patients and characteristics of the disease at the acute phase by the Peritraumatic Dissociative Experience Questionnaire (PDEQ) and Peritraumatic Distress Inventory (PDI) and the degree of impairment on the Sheehan Disability Scale. Results: We initially included 32 of 80 patients admitted during the study period. At 6 months, seven of 30 still followed up had a PTSD Checklist score > 44, suggesting a PTSD prevalence of 23%; 23 (77%) patients had a hydroxyzine prescription at the acute phase. The main risk factors associated with PTSD at 6 months were psychological results at the acute phase. Conclusions: Despite frequent prescription of hydroxyzine at the acute phase, almost one‐quarter of patients with SJS/TEN had PTSD at 6 months. A systematic psychiatric evaluation should be offered regularly for at least 1 year after the acute disease phase. Abstract : What's already known about this topic? Epidermal necrolysis, comprising Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), is a rare and severe cutaneous adverse reaction with long‐term somatic consequences and still underrecognized psychological complications. What does this study add? We conducted a prospective study including 31 (32 initially) adults with SJS/TEN and found a 23% prevalence of post‐traumatic stress disorder at 6 months after the acute disease phase. Risk factors were high scores of peritraumatic emotional reaction and dissociation at the acute phase but not age, sex or initial severity of the disease. Plain language summary available online Respond to this article